The role of ICT in modulating the effect of education and lifelong learning on income inequality and economic growth in Africa - Vanessa Tchamyou; Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2019)
This study assesses the role of ICT in modulating the impact of education and lifelong learning on income inequality and economic growth. It focuses on a sample of 48 African countries from 2004 to 2014. The empirical evidence is based on the generalised method of moments (GMM). The following findings are established. First, mobile phone and internet each interact with primary school education to decrease income inequality. Second, all ICT indicators interact with secondary school education to exert a negative impact on the Gini index. Third, fixed broadband distinctly interacts with primary school education and lifelong learning to have a positive effect on economic growth. Fourth, ICT indicators do not significantly influence inequality and economic growth through tertiary school education and lifelong learning. These main findings are further substantiated. Policy implications are discussed.
Keywords: I28; I20; I30; L96; O55; 330; Education; Lifelong learning; ICT; Inequality; Africa